2007
DOI: 10.1002/chir.20416
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of enantiopure 2‐aryl‐2‐methoxypropionic acids and determination of their absolute configurations by X‐ray crystallography

Abstract: Racemic 2-aryl-2-methoxypropionic acids were enantioresolved by the use of (S)-(-)-phenylalaninol 4. For instance, racemic 2-methoxy-2-phenylpropionic acid (+/-)-7 was condensed with phenylalaninol (S)-(-)-4 yielding a diastereomeric mixture of amides, which was easily separated by HPLC on silica gel affording the first-eluted amide (-)-13a and the second-eluted amide (+)-13b: alpha = 3.19, Rs = 3.49. The absolute configuration of amide (-)-13a was determined to be (R;S) by X-ray crystallography by reference t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 19 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…26 In addition to the methoxyassisted salt bridge (see above), conventional salt bridges were observed between the ammonium and carboxylato groups: both the interatomic distances between H23/O1 and H24/O2 were 1.87 (3) A. A CH/O interaction was observed between H17, the hydrogen atom in the methyl group of PEA cation and the neighbouring carboxylate oxygen atom O1 at a distance of 2.39 (3) A. Furthermore, a CH/p interaction was observed between H14, the hydrogen atom attached to the chiral centre of PEA cation and the neighbouring naphthyl group at a distance of 2.9 A.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…26 In addition to the methoxyassisted salt bridge (see above), conventional salt bridges were observed between the ammonium and carboxylato groups: both the interatomic distances between H23/O1 and H24/O2 were 1.87 (3) A. A CH/O interaction was observed between H17, the hydrogen atom in the methyl group of PEA cation and the neighbouring carboxylate oxygen atom O1 at a distance of 2.39 (3) A. Furthermore, a CH/p interaction was observed between H14, the hydrogen atom attached to the chiral centre of PEA cation and the neighbouring naphthyl group at a distance of 2.9 A.…”
Section: Resultsmentioning
confidence: 98%
“…11 The carboxy groups of (S)-3 formed a chain-like motif called a catemer. 10 X-Ray crystallographic data and NMR spectra of the (R)-MaNP amide 3,11 suggested that the methine group of the amine moiety and the carbonyl group were syn, while the carbonyl and the methoxy groups were anti (Fig. 9 The crystalline conformation of the (S)-MaNP ester was similar to those of acids (S)-1 and (S)-3 as follows (Fig.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations